2017
DOI: 10.3390/ijms18112403
|View full text |Cite
|
Sign up to set email alerts
|

Physical Localization of a Locus from Agropyron cristatum Conferring Resistance to Stripe Rust in Common Wheat

Abstract: Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most destructive diseases of wheat (Triticum aestivum L.) worldwide. Agropyron cristatum (L.) Gaertn. (2n = 28, PPPP), one of the wild relatives of wheat, exhibits resistance to stripe rust. In this study, wheat-A. cristatum 6P disomic addition line 4844-12 also exhibited resistance to stripe rust. To identify the stripe rust resistance locus from A. cristatum 6P, ten translocation lines, five deletion lines and the BC2F2 and BC3F2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…A number of agronomically important traits were identified in Agropyron spp., including resistance to pests and diseases such as barley yellow dwarf virus (Sharma et al 1984; Shukle et al 1987), wheat streak mosaic virus (Sharma et al 1984; Brettell et al 1988; Triebe et al 1991), yellow rust, leaf rust and stem rust (Knott 1964, 1968; Cauderon and Rhind 1976; Whelan 1988; Friebe et al 1992; Zhang et al 2017), powdery mildew (Copete and Cabrera 2017) and tolerance to different abiotic stresses like cold (Limin and Fowler 1987), salinity (Dewey 1960, 1962; McGuire and Dvořák 1981; Forster et al 1987; Littlejohn 1988) and drought (Dewey 1984) and genes affecting yield (Song et al 2013). These traits would be desirable to transfer into wheat by interspecific hybridization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of agronomically important traits were identified in Agropyron spp., including resistance to pests and diseases such as barley yellow dwarf virus (Sharma et al 1984; Shukle et al 1987), wheat streak mosaic virus (Sharma et al 1984; Brettell et al 1988; Triebe et al 1991), yellow rust, leaf rust and stem rust (Knott 1964, 1968; Cauderon and Rhind 1976; Whelan 1988; Friebe et al 1992; Zhang et al 2017), powdery mildew (Copete and Cabrera 2017) and tolerance to different abiotic stresses like cold (Limin and Fowler 1987), salinity (Dewey 1960, 1962; McGuire and Dvořák 1981; Forster et al 1987; Littlejohn 1988) and drought (Dewey 1984) and genes affecting yield (Song et al 2013). These traits would be desirable to transfer into wheat by interspecific hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, production of wheat– A. cristatum translocation lines was reported by Luan et al (2010) and Song et al (2013). In these studies, the chromosome 6P has been identified as the carrier of genes controlling yield components including the number of florets and kernels per spike (Luan et al 2010) and of a locus conferring resistance to stripe rust (Zhang et al 2017). Ochoa et al (2015) developed another line, TH4, which carries a Robertsonian translocation involving the long arm of wheat chromosome 1B and the short arm of an unidentified tetraploid A. cristatum chromosome, with substantial resistance to leaf rust.…”
Section: Introductionmentioning
confidence: 99%
“…As the wild‐crop relatives have not been subjected to human selection, they exhibit large genetic variation and offer a rich source of alleles and genes for crop improvement (Tanksley and McCouch, 1997). Alien gene transfer through chromosome engineering is an effective strategy to exploit this wild genetic diversity for wheat improvement (Feuillet et al, 2008; Luan et al, 2010; Molnár‐Láng et al, 2015; Ochoa et al, 2015; Zhang et al, 2017).…”
mentioning
confidence: 99%
“…Fukuhokumugi (Fukuho) and A. cristatum accession Z559 and embryo rescue [11]. Several of these lines, including additional lines, disomic substitution lines, translocation lines and introgression lines, exhibit potentially valuable traits for wheat improvement, such as disease resistance, abiotic and biotic stress tolerance and high yield and have been used in wheatbreeding programmes [12][13][14][15]. Among these lines, Pubing 3035, a Ti1AS-6PL-1AS·1AL intercalary translocation, was derived from the offspring of a wheat-A.…”
Section: Introductionmentioning
confidence: 99%